Enantioselective synthesis of spiro[4.4]non- and spiro[4.5]dec-2-ene-1,6-diones - B. Chitkul (2018)
Spiro[4.4]non- and spiro[4.5] dec-2-ene-1,6-diones [2; n = 0 and 1] were prepared in moderate to high enantiomeric purities via asymmetric allylation of enamines 6 and ketal derivatives 7 and 8 formed from keto-esters 5, followed by a carbanionic cyclization process. © 1994.